1973
DOI: 10.1111/j.1467-9450.1973.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of stress‐inducing instructions on anxiety, learning and performance

Abstract: Marton, F. I., Fransson, A., Jonsson, B., Klenell, A.‐Ch. & Roos, B. Differential effects of stress‐inducing instructions on anxiety, learning and performance. Scand. J. Psychol., 1973, 14, 213–219.‐In an attempt to investigate the effects of induced stress on anxiety, learning and performance, the separate effects on the learning and performance phases were obtained by varying the timing of the introduction and the removal of stressinducing instructions. Stess‐inducing instructions had a positive effect on le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Anxiety is one of the themes around which there has been a marked research interest in several Scandinavian psychological laboratories. In Gothenburg (Sweden) Marton et al ( 1973) have been interested in stress-inducing instructions on learning. In Turku (Finland) von Wright & Vauras (1980) have concentrated on stress-inducing noise, neuroticism and recall from memory.…”
Section: Anxietymentioning
confidence: 99%
“…Anxiety is one of the themes around which there has been a marked research interest in several Scandinavian psychological laboratories. In Gothenburg (Sweden) Marton et al ( 1973) have been interested in stress-inducing instructions on learning. In Turku (Finland) von Wright & Vauras (1980) have concentrated on stress-inducing noise, neuroticism and recall from memory.…”
Section: Anxietymentioning
confidence: 99%
“…Day, Michaels, and Joachimsthaler () stated that role conflict raises performance and Gmelch and Chan () explored ways to generate proper amounts of stress for optimum stimulation and performance. In a similar line of study, researchers have suggested and found that moderate stress levels best explain that individual effectiveness (Zulkifli & Siegel, ) and differential effects of stressors on a host of other constructs have been in the research dialog for quite some time (Marton, Fransson, Jonsson, Clenell, & Roos, ).…”
mentioning
confidence: 96%
“…have been in the research dialog for quite some time (Marton, Fransson, Jonsson, Clenell, & Roos, 1973).…”
mentioning
confidence: 99%